2005
DOI: 10.1186/1471-2458-5-120
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic physicians' tobacco intervention practices: a cross-sectional survey study

Abstract: Background: U.S. Hispanic physicians constitute a considerable professional collective, and they may be most suited to attend to the health education needs of the growing U.S. Hispanic population. These educational needs include tobacco use prevention and smoking cessation. However, there is a lack of information on Hispanic physicians' tobacco intervention practices, their level of awareness and use of cessation protocols, and the type of programs that would best address their tobacco training needs. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
1
23
3
1
Order By: Relevance
“…The present study also revealed that few physicians set quit dates for their patients, which is in agreement with the findings of other studies. (15,21) In our study, the most common method of intervention was brief advice, which was reportedly given by 61.5% of physicians as a method of smoking cessation, a considerably lower proportion than the 95.8% reported in a study conducted in Canada. (22) The use of NRT by 2.8% was very low when compared with the 25% reported in Norway and the 95.8% reported in Canada.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The present study also revealed that few physicians set quit dates for their patients, which is in agreement with the findings of other studies. (15,21) In our study, the most common method of intervention was brief advice, which was reportedly given by 61.5% of physicians as a method of smoking cessation, a considerably lower proportion than the 95.8% reported in a study conducted in Canada. (22) The use of NRT by 2.8% was very low when compared with the 25% reported in Norway and the 95.8% reported in Canada.…”
Section: Discussioncontrasting
confidence: 42%
“…A significant proportion of physicians reported asking their patients about tobacco use, which is higher than the 44-48% reported in other studies. (15,21) However, only 39.4% asked their patients about the reasons for using tobacco. Failure to ask about the reasons for using tobacco denies physicians the opportunity of recommending the appropriate method of intervention, anticipating challenges during the stages of quitting and enlisting the necessary clinical and social support.…”
Section: Discussionmentioning
confidence: 99%
“…In Bosnia and Herzegovina, there were 40% of physicians and 51% of nurses who smoke 24 . The lowest prevalence was recorded in the USA, Great Britain and Australia with only 3% of smokers, and New Zealand with only 5% [25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] While close to one quarter of respondents ask parents about tobacco use, only 14% always advise parents to quit, and less than 5% always provide assistance in quitting. In contrast to studies with physicians, [18][19][20] our sample cited parent resistance, parent anger, and lack of tobacco cessation materials as the most significant barriers to routine provision of tobacco cessation interventions.…”
Section: Discussionmentioning
confidence: 50%